SISTEM INFORMASIPENDUKUNG KEPUTUSAN PEMILIHAN PELANGGAN TERBAIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA MINIMARKET UTAMA KENDAL - Teguh Setiadi; Hendri Rasminto; Siti Ulfatur Rohmah (Lembaga Pengembangan Kinerja Dosen, 2022)
The Kendal Main Minimarket, which is located at Sendang Kulon Village, RT 02/02, Kangkung District, Kendal Regency, is an alternative place to shop and look for daily needs. The obstacle faced by the company is the selection of active customers who are given an annual bonus at random, therefore there are still many customers who complain because they feel they often shop but do not get the annual bonus. Based on this research, the authors designed and made the application of the best customer selection decision support system using the Simple Additive Weighting method with the aim of making recording and selecting customers easier and more effective. This application uses notepad++ software as a text editor and MySQL database.